PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA TENAGA KEPENDIDIKAN UIN SUNAN AMPEL SURABAYA - Wibowo, Eko Wahyu; Rahayu, Sri; Fitrianty, Rifda (ITB AAS Indonesia Surakarta, 2025)
This study examines the influence of leadership style and work environment on job satisfaction, with work motivation as an intervening variable, among educational staff at Sunan Ampel State Islamic University, Surabaya. The method used is quantitative with a path analysis approach to understand the causal relationships between independent, intervening, and dependent variables. The research sample consisted of educational staff selected through proportional stratified random sampling. The results indicate that leadership style significantly influences work motivation and job satisfaction. Furthermore, the work environment also has a significant impact on work motivation and job satisfaction. Work motivation is proven to mediate the relationship between leadership style and the work environment with job satisfaction. Further analysis reveals that a combination of transformational leadership style and a conducive work environment can enhance the work motivation of educational staff, which in turn strengthens their job satisfaction. This research contributes by providing a more comprehensive understanding of the interaction of these variables in the context of Islamic higher education institutions. This study offers practical implications for institutional managers in designing strategies for improving job satisfaction through optimizing leadership style, improving the work environment, and enhancing work motivation. Additionally, this research enriches the literature on human resource management, particularly concerning the role of intervening variables in job satisfaction models.